Анализ оптимальных режимов работы силовых трансформаторов в условиях эксплуатации - Хоменко, Игорь Васильевич; Березка, Сергей Константинович; Поляков, Игорь Владимирович (НТУ "ХПИ", 2016)
Приведены теоретические и практические положения оптимальности режимов работы трансформаторного оборудования на подстанции при их параллельной работе. Расчеты адаптированы для реальных условий эксплуатации для энергетики Украины.

Purpose. The study of parallel operation optimal modes of transformer equipment for a variety of operating conditions: same or different types of transformers, with or without reactive power flows. Methodology. Losses of energy in transformers make 30 % of all losses. Therefore the choice of the economically justified parallel operation of transformers is effective action to reduce losses. Typically, in the calculations of reactive power flows in the transformers are not taken into account. It is interesting to analyze the optimal operating conditions of transformers with and without reactive power flows. Results. Calculations for transformers in distribution networks showed that the inclusion of reactive power flows in transformers significant impact on the calculated optimum regimes of transformers.
Analysis of optimum operating modes of power transformers under operating conditions
Keywords: трансформаторное оборудование; параллельная работа; оптимальный режим; реактивная мощность; экономически целесообразный режим; transformer equipment; parallel operation; optimal mode; reactive power; economically reasonable mode